Peran pendidikan dalam identitas nasional - Safi’i, Nadira Alya (Maliki Interdisciplinary Journal, 2025)
Education holds a highly strategic position in the formation and reinforcement of a nation’s national identity. In the context of Indonesia as a multicultural country, education functions as an integrative medium capable of unifying cultural, ethnic, religious, and linguistic diversity within a single national identity framework. This study aims to examine in depth the role of both formal and non-formal education in shaping collective awareness of national identity, instilling the values of Pancasila, and fostering a sense of patriotism and pride in being part of the Indonesian nation. This research employs a qualitative approach through literature study and analysis of national education policies. The findings reveal that an educational curriculum containing local content, civic education, and the study of national history significantly influences the formation of students’ national identity. Moreover, education contributes to the internalization of noble national values through social interaction within schools and communities. Education is not merely a transmission of knowledge but also a cultural process that instills identity and character in the younger generation. In the era of globalization and the rapid advancement of information technology, challenges to the existence of national identity are increasingly significant. Therefore, education must be adaptive and innovative to remain relevant in strengthening national identity without neglecting openness to global changes. Thus, education oriented towards reinforcing national identity serves as a fundamental pillar in maintaining the unity, sovereignty, and sustainability of the Indonesian nation in the future.